Sertoli–Leydig cell tumors: hormonal profile after dynamic test with GnRH analogue: triptorelin represents a useful tool to evaluate tumoral hyperandrogenism. (January 2015) - Turra, J.; Granzotto, M.; Gallea, M.; Faggian, D.; Conte, L.; Litta, P.; Vettor, R.; Mioni, R.
Abstract We report the case of a 15-year-old woman with signs of hyperandrogenism affected by a Sertoli–Leydig cell tumor (SLCT). In our patient, blood analysis showed a high testosterone (T) level (T: 8.53 nmol/L; nv < 1.87 nmol/L) while the GnRH-analogue test demonstrated an exaggerated secretion of 17-hydroxyprogesterone (OHP), T, and androstenedione (A) by the ovary after stimulation. We compared the GnRH-analogue test of our patient with that obtained in a group of normal and healthy women (no. 8 subjects, 16–26 years old), men (no. 4 subjects, 18–28 years old), and in a group of PCOS patients with age and body weight compared. We found in our patient a value of OHP, 17-beta estradiol (E2) and T, from 2 to 18 times higher than healthy women. When we compared our patient with healthy men, we differently observed a comparable response of T. The response of our patient was also comparable with that observed in the PCOS group for E2. During the post-surgical follow up, the GnRH-analogue test of our patient showed a response of OHP, T, and E2 comparable with that of the PCOS group. The GnRH-analogue test is a useful tool to characterize steroidogenesis in SLCT.